2021
DOI: 10.1101/gad.346973.120
|View full text |Cite
|
Sign up to set email alerts
|

Dietary interventions as regulators of stem cell behavior in homeostasis and disease

Abstract: Stem cells maintain tissues by balancing self-renewal with differentiation. A stem cell's local microenvironment, or niche, informs stem cell behavior and receives inputs at multiple levels. Increasingly, it is becoming clear that the overall metabolic status of an organism or metabolites themselves can function as integral members of the niche to alter stem cell fate. Macroscopic dietary interventions such as caloric restriction, the ketogenic diet, and a high-fat diet systemically alter an organism's metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 107 publications
0
22
0
Order By: Relevance
“…DR could decrease circulating levels of growth factors, anabolic hormones, inflammatory cytokines, and oxidative stress markers associated with various malignancies, exerting multiple suppressive effects on both target cells and microenvironments during carcinogenesis [ 83 ]. It is well known that dietary intervention was a regulator of stem cell behavior [ 84 ]. DR was able to restrict increase in hematopoietic stem and progenitor cells and formation of myeloid colony in mouse bone marrow [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…DR could decrease circulating levels of growth factors, anabolic hormones, inflammatory cytokines, and oxidative stress markers associated with various malignancies, exerting multiple suppressive effects on both target cells and microenvironments during carcinogenesis [ 83 ]. It is well known that dietary intervention was a regulator of stem cell behavior [ 84 ]. DR was able to restrict increase in hematopoietic stem and progenitor cells and formation of myeloid colony in mouse bone marrow [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, intracellular metabolites, such as acetyl-CoA, regulate both metabolic pathways and epigenetic processes [ 48 ], thus connecting diet and metabolism with SC functions. This connection is particularly relevant in fate determination for different types of SCs, as SC self-renewal can be achieved by modifying calories or nutrients [ 16 ] and skeletal MuSCs from calorie-restricted mice are more efficient in inducing muscle regeneration than those from ad-libitum-fed mice in transplantation experiments [ 12 ]. Similarly, induced pluripotent stem cells (iPSCs) can be reprogrammed by manipulating metabolic pathways [ 14 ]; whereas MuSC activation requires the shift from fatty acid oxidation (FAO) to glycolysis [ 49 ], the upregulation of glycolytic pathways, as well as the inhibition of mitochondrial activity, may be sufficient to induce stemness features in iPSCs and ESCs [ 50 , 51 , 52 ].…”
Section: Molecular and Cellular Effects Of Diet On Stem Cellsmentioning
confidence: 99%
“…Given the pivotal role of SCs in cancer onset and the well-recognized effect of CR on SC self-renewal [ 16 ], it is worth mentioning that CR and CR mimetics (CRMs) have been studied in the context of CSC generation [ 66 ]. Indeed, it has been demonstrated that CR reduces tumorigenesis in breast tissues and inhibits mammary SC self-renewal, thus reducing progenitor cell number [ 178 ].…”
Section: Effects Of Specific Diets On Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…From human medical point of view, nutritional changes may influence to several aspects. They include macroscopic dietary interventions such as Low Carbohydrate Diet (LCD), Ketogenic Diet (KD), Calorie Restriction (CR), a high-fat meal [1]. LCD and KD bring elevated ketone bodies (KB) in the blood, hyperketonemia [2].…”
mentioning
confidence: 99%